Fabrication of a drug delivery system that enhances antifungal drug corneal penetration - Jingguo Li; Zhanrong Li; Zhen Liang; Lei Han; Huayang Feng; Siyu He; Junjie Zhang (Taylor & Francis Group, 2018)
Fungal keratitis (FK) remains a severe eye disease, and effective therapies are limited by drug shortages and critical ocular barriers. Despite the high antifungal potency and broad spectrum of econazole, its strong irritant and insolubility in water hinder its ocular application. We designed and fabricated a new drug delivery system based on a polymeric vector for the ocular antifungal application of econazole. This novel system integrates the advantages of its constituent units and exhibits superior comprehensive performance. Using the new system, drug content was significantly increased more than 600 folds. The results of in vivo and in vitro experiments demonstrated that the econazole-loaded formulation exhibited significantly enhanced corneal penetration after a single topical ocular administration, excellent antifungal activity, and good tolerance in rabbits. Drug concentrations and ocular relative bioavailability in the cornea were 59- and 29-time greater than those in the control group, respectively. Following the topical administration of one eye drop (50 μL of 0.3% w/v econazole) in fungus-infected rabbits, a high concentration of antimycotic drugs in the cornea and aqueous humor was sustained and effective for 4 h. The mechanism of corneal penetration was also explored using dual fluorescent labeling. This novel drug delivery system is a promising therapeutic approach for oculomycosis and could serve as a candidate strategy for use with various hydrophobic drugs to overcome barriers in the treatment of many other ocular diseases.